Switching to self-employment can be good for your health - Nikolova, Milena (Journal of Business Venturing, 2019)
Relying on theoretical insights from the Job Demand-Control model, which links occupational characteristics to health, this paper provides the first causal evidence of the physical and mental health consequences of self-employment. I utilize German longitudinal data for the period 2002–2014 and difference-in-differences estimations to study switches from unemployment to self-employment (necessity entrepreneurship) and transitions from regular- to self-employment (opportunity entrepreneurship). I find that necessity entrepreneurs experience improvements in their mental but not physical health, while opportunity entrepreneurship leads to both physical and mental health gains. Importantly, the health improvements cannot be explained by changes in income or working conditions and are not driven by personality and risk preferences or the local unemployment conditions. As such, the findings highlight an additional non-monetary benefit of self-employment and have implications for entrepreneurship theory and practice, current and would-be entrepreneurs, as well as policy-makers.